Thermal Plasticity and Evolutionary Constraints in Bacillus: Implications for Climate Change Adaptation - Enrique Hurtado-Bautista; Africa Islas-Robles; Gabriel Moreno-Hagelsieb; Gabriela Olmedo-Alvarez (Biology)
The ongoing rise in global temperatures poses significant challenges to ecosystems, particularly impacting bacterial communities that are central to biogeochemical cycles. The resilience of wild mesophilic bacteria to temperature increases of 2–4 °C remains poorly understood. In this study, we conducted experimental evolution on six wild Bacillus strains from two lineages (Bacillus cereus and Bacillus subtilis) to examine their thermal adaptation strategies. We exposed the bacteria to gradually increasing temperatures to assess their thermal plasticity, focusing on the genetic mechanisms underlying adaptation. While B. subtilis lineages improved growth at highly critical temperatures, only one increased its thermal niche to 4 °C above their natural range. This finding is concerning given climate change projections. B. cereus strains exhibited higher mutation rates but were not able to grow at increasing temperatures, while B. subtilis required fewer genetic changes to increase heat tolerance, indicating distinct adaptive strategies. We observed convergent evolution in five evolved lines, with mutations in genes involved in c-di-AMP synthesis, which is crucial for potassium transport, implicating this chemical messenger for the first time in heat tolerance. These insights highlight the vulnerability of bacteria to climate change and underscore the importance of genetic background in shaping thermal adaptation.